Opportunity recognition among migrant entrepreneurs: Household, community and the haphazard nature of migrants' entrepreneurial decisions. (August 2018) - Lassalle, Paul
This article examines the decision-making process of Polish migrant entrepreneurs (MEs) using the theoretical lens of opportunity recognition, which has not yet been applied to MEs. First, the article provides empirical evidence on Polish MEs in Glasgow on the incremental nature of their entrepreneurial decisions, their ability to perceive opportunities in the community niche market located in the local opportunity structure and the role played by the household context, highlighting that starting-up is a household and not an individual decision. Second, building on the opportunity recognition literature, the article proposes the concept of haphazard entrepreneurship in the case of MEs. The concept encompasses notions of serendipity and mixed embeddedness and recognizes the importance of household migration and settlement strategies in entrepreneurial decision-making.